Training Needs Assessment on Management of Stunting Reduction Program in Indonesia - Februhartanty, Judhiastuty; Birahmatika, Fitya Safira; Fauzia, Khalida; Pramesthi, Indriya Laras; Khusun, Helda; Nurlita, Hera; Hidayat, Ahmad Thohir; Budiharjo, Teguh; Priyatno, Djoko; Sugihantono, Anung; Mansyur, Muchtaruddin (Journal of Health Education, 2024)
Background: Stunting has become a priority in Indonesia's development agenda that national and sub-national teams are established with multi-sectoral involvement to tackle the problem However, coordination hurdles, particularly at the mid-level, underscore the need for understanding frontline workers' capacity, prompting a study to conduct a training needs assessment (TNA) to bolster local governments' commitment to stunting and nutrition promotion. Methods: The TNA was conducted from July to November 2021 employing online quantitative survey and series of focus group discussions (FGDs) among central and local government officers. Quantitative data were about knowledge on stunting, attitudes toward program management, performance assessment, and capacity building needs. The FGDs focused stunting reduction program management and implementation capacity. Results: The present study highlighted the personal and organizational aspects of the management of stunting reduction program in Indonesia. The findings from both aspects were used to understand the needs and gaps revealed so that a relevant and appropriate training/capacity building program can be proposed. Conclusions: Capacity building is required to enhance local governments' commitment to stunting and nutrition promotion programs, particularly focusing on middle management to improve communication and foster multi-sectoral collaboration. Such efforts necessitate a team-based training program to develop skills in coordination and interprofessional collaboration. KEYWORDS: interprofessional collaboration; multi-sectoral involvement; stunting; Training Needs Assessment; Indonesia